2015
DOI: 10.1177/1934578x1501000901
|View full text |Cite
|
Sign up to set email alerts
|

Alarm Pheromone Activity of Nymph-specific Geraniol in Chrysanthemum Lace Bug Corythucha marmorata against Adults and Nymphs

Abstract: The exotic insect pest Corythucha marmorata (Uhler) is increasingly spreading in Japan using the weed Solidago canadensis L. as a major host plant. The nymphs form colonies on the backs of leaves where they crowd together; however, aggregation does not occur in the adults. When an individual nymph is crushed using a needle tip and further the needle tip covered with the nymph's bodily fluids is moved slowly toward the center of the crowd, the surrounding nymphs display an escape behavior and their aggregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…For example, sycamore lace bug nymphs crowd together on the leaves of platanus trees and show evasive behavior when an individual in the center of the crowd is squashed and emits geraniol (Kuwahara et al, 2011 ). Interestingly, geraniol is also the alarm pheromone of the chrysanthemum lace bug, Corythucha marmorata , which is a new exotic invasive pest in Asia (Watanabe and Shimizu, 2015 ), and one of the alarm pheromones in the hawthorn lace bug, Corythucha cydoniae , and eggplant lace bug, Gargaphia solani (Aldrich et al, 1991 ). Thus, geraniol may be common to insect species in Tingidae.…”
Section: Introductionmentioning
confidence: 99%
“…For example, sycamore lace bug nymphs crowd together on the leaves of platanus trees and show evasive behavior when an individual in the center of the crowd is squashed and emits geraniol (Kuwahara et al, 2011 ). Interestingly, geraniol is also the alarm pheromone of the chrysanthemum lace bug, Corythucha marmorata , which is a new exotic invasive pest in Asia (Watanabe and Shimizu, 2015 ), and one of the alarm pheromones in the hawthorn lace bug, Corythucha cydoniae , and eggplant lace bug, Gargaphia solani (Aldrich et al, 1991 ). Thus, geraniol may be common to insect species in Tingidae.…”
Section: Introductionmentioning
confidence: 99%
“…marmorata indicated that females and males produce a specific component with a retention time of 8.769 min (Fig. 3) that is not present in the hexane extract from nymphs 6 . No qualitative sexual differences were identified in the GC profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Some species of Tingidae are known to use the alarm pheromone for conspecific communication 69 ; however, the sex pheromone related to sexual excitation has not yet been elucidated. The presented results demonstrated that the volatile secretions from the adult play a crucial role in the mounting behaviour of C .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations